Incidencia de la conducta suicida en la salud mental de una mujer de 22 años del Recinto San Antonio del Cantón Montalvo - Guizado Chimbo, Mirian Verónica (2023)
The study "Incidence of Suicidal Behavior in the Mental Health of a 22-Year-Old Woman from the San Antonio Area of Montalvo Canton" aims to Determine the incidence of suicidal behavior in the mental health of a 22-year-old woman residing in the San Antonio area of Montalvo Canton. This was a descriptive, qualitative study in which techniques and instruments such as interviews, clinical observation, psychometric tests, Beck II Depression Inventory, and Rosenberg Self-Esteem Inventory were used. The result of the psychometric tests and the information collected from the clinical history, interview, and clinical observation conducted on the patient led to the diagnosis of F34.1 Persistent Depressive Disorder, meeting diagnostic criteria A and B within the DSM-V and ICD-10, where the patient presents low self-esteem, feelings of hopelessness, reduced appetite, insomnia, and lack of concentration. In conclusion, the identification of suicidal behavior was achieved through data collection and direct observation. This result demonstrates the effectiveness of the techniques used to identify and assess suicidal behavior in a clinical context.